2005
DOI: 10.4315/0362-028x-68.10.2208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Typical and Atypical Escherichia coli from Fish Sold at Retail in Cochin, India

Abstract: Escherichia coli is a common contaminant of seafood in the tropics and is often encountered in high numbers. The count of E. coli as well as verotoxigenic E. coli O157:H7 was estimated in 414 finfish samples composed of 23 species of fresh fish from retail markets and frozen fish from cold storage outlets in and around Cochin, India. A total of 484 presumptive E. coli were isolated, and their indole-methyl red-Voges-Proskauer-citrate (IMViC) pattern was determined. These strains were also tested for labile tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
3
27
2
2
Order By: Relevance
“…[41] [42] also found that bacteria belonging to Enterobacteriaceae family were the predominant isolates in the fish samples. [43] found that microbial quality of the tilapia indicated that all tissue samples except muscle tissues were contaminated with fecal coliforms where Escherichia coli is the most common contaminant and is often encountered in high numbers. [44] found that total coliforms count range in fish was between 3.0 × 10 3 -7.5 × 10 6…”
Section: Discussionmentioning
confidence: 99%
“…[41] [42] also found that bacteria belonging to Enterobacteriaceae family were the predominant isolates in the fish samples. [43] found that microbial quality of the tilapia indicated that all tissue samples except muscle tissues were contaminated with fecal coliforms where Escherichia coli is the most common contaminant and is often encountered in high numbers. [44] found that total coliforms count range in fish was between 3.0 × 10 3 -7.5 × 10 6…”
Section: Discussionmentioning
confidence: 99%
“…Shellfish, due to their filter feeding ability, pose a significant risk to human infection since they can concentrate and retain pathogens (4,130). Numerous studies have reported the recovery of both O157 and non-O157 STEC from the carcass of fish and shellfish offered for sale (131)(132)(133)(134)(135).…”
Section: Fish and Shellfishmentioning
confidence: 99%
“…According to Thampuran et al [26], E. coli is commonly associated with seafood contamination in the tropics, where it is encountered in high numbers. The authors isolated E. coli in finfish samples acquired at the retail market in Cochin (India) and, although typical E. coli O157 or labile toxin-producing E. coli were not detected, the isolation of strains with the ability to produce hemolysis in human blood was a fact worth mentioning.…”
Section: Escherichia Coli In Fishmentioning
confidence: 99%